Analisis Risiko Kehilangan Hasil dari Lada Hibrida Tahan Busuk Pangkal Batang - Abdul Muis Hasibuan; Dewi Listyati; Agus Wahyudi (Pusat Penelitian dan Pengembangan Perkebunan, 2011)
Pepper foot rot disease is the major cause of low productivity of pepper plantation in Indonesia. This research aimed to know level of production risk due to foot rot disease and opportunity of pepper hybrids that resistant to foot rot disease to reduce the risk. The research conducted at July – October 2010 in North Lampung District, using survey to pepper farmers. The method use is descriptive and risk analysis. Result showed that farmer faced high production risk cause of foot rot disease attack with average 26 percent and standard deviation 23 percent. There was correlation between foot rot disease attack with pepper productivity. As a response to production risk, introduction of pepper hybrid that resistant to foot rot disease technology has high potential to reduce production risk.